KONTESTASI NARASI KEBIJAKAN PUBLIK DI MEDIA ONLINE TERHADAP PEMBERITAAN KLARIFIKASI PEMERINTAH ATAS KRITIK BEM UGM - Ifazira Hawawi; Hafizh Daffa Al-Fakhri; Julius Christoforus Jae; Alda Ayu Putri Astuti; La Ode Muhammad Erdin; Malik Ibrahim (Yayasan Nusantara Hasana Berdikari, 2026)
This article examines the contestation of public policy narratives in online media through news coverage of government clarifications responding to BEM UGM's criticism. The study focuses on one issue cycle related to the Free Nutritious Meals policy and compares 13 online media outlets, each represented by one news text. Using Zhongdang Pan and Gerald M. Kosicki's framing model, the study analyzes syntactical, script, thematic, and rhetorical structures in the texts. This research applies a qualitative descriptive method within a constructivist paradigm. The findings show three dominant framing tendencies. First, several media place government clarification as an ethical reminder about how criticism should be delivered. Second, one cluster frames clarification as a technical and moral defense of the policy. Third, several media place student criticism, humanitarian concerns, and democratic freedom at the center of the narrative.